2022
DOI: 10.1111/1750-3841.16077
|View full text |Cite
|
Sign up to set email alerts
|

Chicken muscle hydrolysate reduces blood pressure in spontaneously hypertensive rats, upregulates ACE2, and ameliorates vascular inflammation, fibrosis, and oxidative stress

Abstract: Spent hens are egg‐laying chicken reaching the end of their egg‐laying cycle and are seen as a by‐product to the egg industry. A spent hen muscle protein hydrolysate prepared by food‐grade thermoase PC10F (SPH‐T) has previously shown antihypertensive potential. In the present work, we further investigated its antihypertensive effect and underlying mechanisms in spontaneously hypertensive rats. There are three groups: untreated, low dose (250 mg SPH‐T/kg/day body weight), and high dose (1,000 mg SPH‐T/kg/day bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 66 publications
1
18
0
Order By: Relevance
“…Ang II and Ang (1−7) concentrations were measured using Elisa kits (CSB-E04494r & CSB-E14241r, Cusabio Technology, Houston, TX, USA). 22 Briefly, A7r5 cells were grown in a 48-well plate until confluence. Afterward, cells were treated with 50 μM of V−F for 1 h followed by co-treatment with the Ang II standard (1 μM) for up to 12 h. Then, cell media were collected and used for Ang II and Ang (1−7) measurement as per the manufacturer's manuals.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ang II and Ang (1−7) concentrations were measured using Elisa kits (CSB-E04494r & CSB-E14241r, Cusabio Technology, Houston, TX, USA). 22 Briefly, A7r5 cells were grown in a 48-well plate until confluence. Afterward, cells were treated with 50 μM of V−F for 1 h followed by co-treatment with the Ang II standard (1 μM) for up to 12 h. Then, cell media were collected and used for Ang II and Ang (1−7) measurement as per the manufacturer's manuals.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…18−21 In our recent work, a spent hen muscle protein hydrolysate has been prepared using thermoase PC10F, possessing great antihypertensive effect in spontaneously hypertensive rats. 19,22 A7r5). 23 Amelioration of vascular inflammation and oxidative stress is beneficial to the treatment of hypertension.…”
Section: ■ Introductionmentioning
confidence: 99%
“…A spent hen muscle protein hydrolysate prepared by thermoase PC10F, a food-grade protease, could significantly reduce blood pressure in spontaneously hypertensive rats over a period of 20 days (Fan et al 2020 ). Associated with the blood pressure reduction were increased plasma ACE2 level, increased vascular expression of ACE2, as well as attenuated inflammation, oxidative stress, and fibrosis (Fan et al 2022 ; Fan and Wu 2020 ). Later, several potent ACEi peptides including Val-Arg-Pro (VRP), Leu-Lys-Tyr (LKY), and Val-Arg-Tyr (VRY), with IC 50 value of 0.034–5.77 μg/mL were identified, as well as a few ACE2u peptides, such as Val-Lys-Trp (VKW), Val-His-Pro-Lys-Glu-Ser-Phe (VHPKESF), and Val-Val-His-Pro-Lys-Glu-Ser-Phe (VVHPKESF), which upregulated vascular ACE2 expression by 0.52–0.84 folds (Fan and Wu 2021b ).…”
Section: Value-added Uses Of Spent Hensmentioning
confidence: 99%
“…We have previously reported that spent hen muscle protein hydrolysate prepared by Protex 50FP generated a hydrophilic fraction, which significantly reduced bitter sensation of quinine and attenuated the activation of bitter taste receptors in HEK 293 cells (Xu et al 2019 ). Another muscle protein hydrolysate prepared by food-grade protease thermoase PC10F possessed weak bitterness but strong umami taste (Fan et al 2022 ). This indicated the applicability of spent hen peptides in food matrices as flavor enhancers or off-flavor masking agents.…”
Section: Value-added Uses Of Spent Hensmentioning
confidence: 99%
“…We have previously reported a spent hen muscle protein hydrolysate prepared by thermoase PC10F, a food-grade protease, and identified four RAS-regulating peptides, including Val-Arg-Pro (VRP), Leu-Lys-Tyr (LKY), Val-Arg-Tyr (VRY), and Val-Val-His-Pro-Lys-Glu-Ser-Phe [VVHPKESF (V-F)]. [16][17][18] However, their abilities in attenuating vascular endothelial inflammation remain unknown. Therefore, the objectives of the present work were to understand the anti-inflammatory effects of VRP, LKY, VRY, and V-F in TNF𝛼-stimulated human vascular endothelial EA.hy926 cells, based on the expression of inflammatory proteins including VCAM-1, ICAM-1, COX2, and inducible nitric oxide synthase (iNOS), as well as intracellular signaling pathways underlying their anti-inflammatory effects.…”
Section: Introductionmentioning
confidence: 99%